The effects of temporal contiguity and expertise on acquisition of tactical movements - Khacharem, Aïmen; Trabelsi, Khaled; Engel, Florian; Sperlich, Billy; Kalyuga, Slava (Frontiers in psychology, 2020)
Various studies demonstrated that multimedia learning improves when text and pictures are presented contiguously in time rather than separately - the temporal contiguity effect. The present study investigated whether this advantage is restricted to only novice learners (novices) or also extends to more knowledgeable learners (expert), and whether it depends on the length of instructional segments. Learners with varied levels of expertise (experts vs. novices) learned about basketball game system in five different experimental conditions. In the first three conditions, an entire video clip and audio text were presented either at the same time or the video clip was presented before or after the entire audio (macro-step presentations). In the remaining two conditions, short segments of the video clip were presented before or after corresponding short segments of the audio (micro-step presentations). Overall, novice learners benefited more from the concurrent presentation (combination of learning and mental effort scores); in addition, and in the case of macro-step presentations novices performed better when the audio segment preceded the video clip segment. However, experts benefited more from the micro-step presentations, demonstrating an expertise reversal effect.
Gesehen am 12.01.2021